Planning Orthopedic Treatment for Patients with Occlusal-Articulation Disorders and Functional Disorders of the Dentofacial System or Pain Syndrome Associated with Temporomandibular Joint Dysfunction - Proshchenko, Andrii (Journal of Education, Health and Sport, 2024)
The number of patients with temporomandibular joint (TMJ) dysfunction increases annually. This trend is largely attributed to the prolonged asymptomatic progression of these disorders and the absence of organic changes in the early stages of the disease, both clinically and radiographically. Scientific perspectives on the etiology and pathogenesis of TMJ dysfunctions remain significantly contradictory. This article highlights the following methodological approaches: Integration of modern diagnostic methods: utilization of cone-beam computed tomography to assess changes in the TMJ, synchrography to study the function of masticatory muscles and the imbalance in their activity depending on occlusal-articulatory relationships before and after prosthetic treatment; Personalized approaches: development of individual treatment protocols based on detailed multidimensional analysis and the creation of predictive models for treatment strategy selection during the preparatory and occlusal therapy stages (decision tree methodology). These protocols are adapted to the severity of disorders in patients and leverage modern digital technologies in dentistry, including the application of CAD/CAM technologies for creating permanent and temporary prosthetic constructions and Digital Smile Design methodology for harmonizing the aesthetic and functional aspects of treatment.